Impact of sexual and reproductive health interventions among young people in sub-Saharan Africa: a scoping review - Chipako, Isaac; Singhal, Saurabh; Hollingsworth, Bruce (Frontiers in Global Women's Health, 2024)
Objectives The aim of this scoping review was to identify and provide an overview of the impact of sexual and reproductive health (SRH) interventions on reproductive health outcomes among young people in sub-Saharan Africa. Methods Searches were carried out in five data bases. The databases were searched using variations and combinations of the following keywords: contraception, family planning, birth control, young people and adolescents. The Cochrane risk-of-bias 2 and Risk of Bias in Non-Randomized Studies-of-Interventions tools were used to assess risk of bias for articles included. Results Community-based programs, mHealth, SRH education, counselling, community health workers, youth friendly health services, economic support and mass media interventions generally had a positive effect on childbirth spacing, modern contraceptive knowledge, modern contraceptive use/uptake, adolescent sexual abstinence, pregnancy and myths and misperceptions about modern contraception. Conclusion Sexual and reproductive health interventions have a positive impact on sexual and reproductive health outcomes. With the increasing popularity of mHealth coupled with the effectiveness of youth friendly health services, future youth SRH interventions could integrate both strategies to improve SRH services access and utilization.